The Reflexes of Syllabic Liquids in Ancient Greek Linguistic Prehistory of the Greek Dialects and Homeric Kunstsprache - van Beek, Lucien (Leiden Studies in Indo-European, 2022)
Reflexes of syllabic liquids play an important yet controversial role in Greek dialect classification and the analysis of Homeric formulas. This book tackles the entire evidence afresh and elaborates a ground-breaking new scenario of language change in the epic tradition.; Readership: The book is a must-have for academic libraries and specialists/researchers in Indo-European Linguistics, Homeric studies (and hence Classics more generally), Mycenology, and Ancient Greek dialectology.